2021
DOI: 10.1371/journal.pone.0249482
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use is associated with smaller hypothalamic and pituitary gland volumes in healthy women: A structural MRI study

Abstract: The effects of hormonal contraceptives on structural features of the hypothalamus and pituitary are incompletely understood. One prior study reported microstructural changes in the hypothalamus with oral contraceptive pill (OCP) use. However, effects on hypothalamic volume have not been reported. One prior study reported volumetric changes in the pituitary. However, this study was limited by including participants evaluated for neurological symptoms. We sought to determine if OCP use is associated with alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In a recent MRI study of midlife women at risk for AD, OC users exhibited greater GM volume in medial temporal lobe, precuneus, fusiform gyrus, parietal and frontal cortex as compared to never-users (Schelbaum et al, 2021), which is in line with findings in younger women . However, other studies reported reduced GM volume of amygdala, parahippocampal gyrus, hypothalamus, pituitary gland, posterior cingulate cortex and orbitofrontal cortex of OC users compared to non-users (Petersen et al, 2015;Lisofsky et al, 2016;Chen et al, 2021). When comparing the follicular phase of naturally cycling women with the inactive phase of androgenic progestins or antiandrogenic pills, OC users had lower GM volume in cingulate gyrus and bilateral culmen, although these effects did not survive correction for multiple 10.3389/fnagi.2022.948219 comparisons (De Bondt et al, 2016).…”
Section: Oral Contraceptivesmentioning
confidence: 86%
“…In a recent MRI study of midlife women at risk for AD, OC users exhibited greater GM volume in medial temporal lobe, precuneus, fusiform gyrus, parietal and frontal cortex as compared to never-users (Schelbaum et al, 2021), which is in line with findings in younger women . However, other studies reported reduced GM volume of amygdala, parahippocampal gyrus, hypothalamus, pituitary gland, posterior cingulate cortex and orbitofrontal cortex of OC users compared to non-users (Petersen et al, 2015;Lisofsky et al, 2016;Chen et al, 2021). When comparing the follicular phase of naturally cycling women with the inactive phase of androgenic progestins or antiandrogenic pills, OC users had lower GM volume in cingulate gyrus and bilateral culmen, although these effects did not survive correction for multiple 10.3389/fnagi.2022.948219 comparisons (De Bondt et al, 2016).…”
Section: Oral Contraceptivesmentioning
confidence: 86%
“…These naturally occurring variations of hormone concentrations in the human body could affect brain morphometry as well. In fact, an exploratory analysis of naturally cycling women revealed volumetric differences of the total hypothalamus during different menstrual cycle phases (Chen et al, 2021). Also other studies showed variations of volumetric findings of the human brain in different menstrual cycle phases of naturally cycling women (De Bondt et al, 2013; Protopopescu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring the effects of OCPs on human brain structure, reported smaller hypothalamic volume in healthy CW with OCP intake compared to naturally cycling CW (Chen et al, 2021). OCP mostly consists of estrogens and progestogens (Dragoman, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it remains unclear how influences of age and physical health in the hypothalamus are temporally related, how one affects the other, and which other participant characteristics could further explain hypothalamic microstructure. For example, potential effects of sleep and hormonal medication (e.g., oral contraceptive use) need to be considered [ 57 , 58 ]. Longitudinal investigations could shed light onto these mechanisms to better understand their individual and shared contributions to better target interventions aiming at healthy aging.…”
Section: Discussionmentioning
confidence: 99%